STRATEGI CONTENT WRITING DALAM MENINGKATKAN DAYA TARIK INSTAGRAM PT INHUTANI I - Difa Nadia Kharisma, Erika; Budi Priatna, Wahyu (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
This research aims to understand the content writing strategy applied in an effort to increase the attractiveness of PT Inhutani I's Instagram social media, as well as knowing the challenges and solutions faced by the company. PT Inhutani I is a State-Owned Enterprise (BUMN) engaged in the forestry sector that utilizes Instagram as a means of communication to the public and company branding since 2017. This research used a qualitative method with a case study approach and is supported by data from in-depth interviews with the company's Communication Department team and audiences. The results showed that the content writing strategy implemented by PT Inhutani I can be analyzed using the AIDA (Attention, Interest, Desire, Action) approach which has been proven to be applied in a well-structured manner through consistent visual content, selection of communicative language styles, and utilization of trends that are aligned. However, the Desire and Action elements still require improvement with the presentation of call-to-actions that need to be strengthened. The challenges faced are the absence of specific writing guidelines, lack of references to the use of forestry technical terms, and limited time in content production. Solutions include cross-team coordination, periodic evaluation, and the preparation of permanent guidelines for content writing. This content writing strategy is highly important for the company because it has great potential in increasing the company's revenue. Keywords: AIDA, BUMN, attractiveness, instagram, content writing strategy Penelitian ini bertujuan untuk memahami strategi content writing yang diterapkan dalam upaya meningkatkan daya tarik media sosial Instagram PT Inhutani I, serta mengetahui adanya tantangan dan solusi yang dihadapi oleh perusahaan. PT Inhutani I sebagai Badan Usaha Milik Negara (BUMN) yang bergerak di bidang kehutanan memanfaatkan media sosial Instagram sebagai sarana komunikasi kepada masyarakat dan branding perusahaan sejak tahun 2017. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus dan didukung melalui data hasil wawancara mendalam kepada tim Departemen Komunikasi perusahaan hingga audiens. Hasil penelitian menunjukkan strategi content writing yang diterapkan oleh PT Inhutani I dapat dianalisis menggunakan pendekatan AIDA (Attention, Interest, Desire, Action) yang telah terbukti diterapkan secara terstruktur baik melalui visual konten yang konsisten, pemilihan gaya bahasa yang komunikatif, serta pemanfaatan tren yang selaras. Namun, pada unsur Desire dan Action masih memerlukan peningkatan dengan penyajian call-to-action yang perlu diperkuat. Tantangan yang dihadapi yaitu belum adanya pedoman khusus penulisan, kurangnya referensi penggunaan istilah teknis kehutanan, dan keterbatasan waktu dalam produksi konten. Solusi yang dapat dilakukan adalah keterlibatan koordinasi lintas tim, evaluasi berkala, serta penyusunan panduan tetap penulisan konten. Strategi content writing ini sangat penting bagi perusahaan karena memiliki potensi besar dalam meningkatkan citra positif perusahaan dan kredibilitas PT Inhutani I dimata publik. Kata Kunci: AIDA, BUMN, daya tarik, instagram, strategi content writing